Your Wish Is My CMD: Artificial intelligence could automate software coding. - Savage, Neil (Communications of the ACM, 2020)
The article explores how as artificial intelligence (AI) techniques advance many tasks previously done by humans will be automated. These tasks include the writing of computer code, meaning professional software engineers will not write code anymore. Other topics discussed include the concept of program synthesis, which dates back to the 1950s, how a lack of data can impede machine learning and the viewpoint that automating software creation could free programmers to focus on the more creative parts of their jobs.